Non-Newtonian fluid quasi-solid electrolyte, preparation method and application

By using non-Newtonian fluid quasi-solid electrolytes and in-situ polymerization technology in metal lithium batteries, the problems of lithium dendrites growth and internal short circuits are solved, and the safety and circulation performance of the battery are significantly improved.

CN119764541AActive Publication Date: 2025-04-04CHINA ELECTRONIC TECH GRP CORP NO 18 RES INST

Patent Information

Application Number
CN202411871859.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-04
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

Metal lithium batteries face safety problems, mainly due to the problems of lithium excision, dead lithium and lithium dendrites caused by the uneven deposition of lithium metal negative electrodes, which affect the balun efficiency and cycle life of the battery and may lead to the combustion and explosion of the battery.

Method used

A non-Newtonian fluid quasi-solid electrolyte is used to perform in-situ polymerization by adding shear thickening raw materials, polymeric monomers, crosslinkers and thermal initiators to the electrolyte to form a polymer network, absorbing stress caused by lithium plating/delithation of the battery, inhibiting the growth of lithium dendrites and preventing internal short circuits.

Benefits of technology

Through the synergy between non-Newtonian fluid and in-situ polymer network, the safety and cycling performance of the battery are significantly improved, preventing the growth of lithium dendrites and internal short circuits, and extending the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764541A_ABST
    Figure CN119764541A_ABST
Patent Text Reader

Abstract

The invention provides a non-Newtonian fluid quasi-solid electrolyte, a preparation method and application, the electrolyte is prepared from the following raw materials: a basic electrolyte, a shear thickening raw material, a polymeric monomer, a cross-linking agent and a thermal initiator, and the mass ratio of the basic electrolyte to the shear thickening raw material is 20: (1-10). The quasi-solid electrolyte with the non-Newtonian fluid characteristic is used for absorbing stress caused by lithium plating / lithium removal of the battery, the volume change of the battery in the charging and discharging process is relieved, mechanical hardening is rapidly generated when the battery is subjected to large-current pulse charging or external sudden bearing, the growth of lithium dendrites is inhibited, and internal short circuit is prevented; a polymer network obtained by carrying out in-situ polymerization on a polymeric monomer, a cross-linking agent, a thermal initiator and the like is adopted, so that battery liquid leakage or oxygenolysis is prevented, metal lithium is deposited and dissolved more uniformly, and the growth of metal lithium dendrites is inhibited; through the synergistic effect of the non-Newtonian fluid and the in-situ polymerized polymer network, the safety performance and the cycle performance of the battery can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal lithium batteries, and in particular to a non-Newtonian fluid quasi-solid electrolyte, a preparation method and an application thereof. Background Art

[0002] With the continuous advancement of global energy conservation and emission reduction and the rapid development of new energy vehicles, the main body of energy utilization has gradually shifted from traditional fossil energy to low-carbon renewable energy. Therefore, the efficient energy storage system based on electrochemical reactions is not restricted by the geographical environment. The development of electrochemical energy storage technology with high energy density and high safety is an important part of the energy revolution represented by renewable energy and new energy vehicle industries. At present, lithium-ion battery technology is highly mature and plays an important role in promoting the process of social intelligence and portability. After nearly three decades of development, the energy density of lithium-ion batteries based on electrochemical intercalation reactions is close to the theoretical limit, but it still cannot meet the energy storage needs of contemporary society. Therefore, it is imperative to develop the next generation of electrode materials with high safety and high specific capacity.

[0003] Lithium metal is considered to be one of the most promising negative electrode materials due to its ultra-high theoretical specific capacity (3860mAh / g) and very low standard negative electrochemical potential (-3.040V). Lithium metal secondary batteries with high specific properties can break through the energy density bottleneck of existing lithium-ion batteries (≤350Wh / kg) and achieve a single cell energy density of ≥500Wh / kg. However, lithium metal batteries face safety issues, mainly lithium plating, dead lithium and lithium dendrites caused by uneven deposition of lithium metal negative electrodes. Uneven deposition of lithium metal affects the coulombic efficiency and cycle life of the battery. Lithium dendrite growth can puncture the diaphragm, causing a short circuit in the battery, thereby causing the battery to burn and explode.

[0004] The problems of metal lithium negative electrode interface stability and dendrite growth can be suppressed by understanding the lithium deposition law and regulating the metal deposition behavior, which can reduce the current density on the electrode surface and induce the uniform deposition of lithium ions, reducing the generation of dendrites; the volume effect during the cycle can be alleviated by a three-dimensional lithium metal negative electrode, and the electrochemical performance of the battery can be improved; the growth of lithium dendrites can be suppressed and the battery performance can be improved by optimizing the electrolyte and constructing an artificial protective film; solid electrolytes can be used to reduce negative electrode interface side reactions and improve battery safety; and the mechanical and chemical compatibility between the electrolyte and the electrode can be improved by preparing a composite electrolyte and introducing an interface modification layer. However, at present, the inhibitory effect of optimizing the electrolyte on lithium dendrites is limited, and the introduction of a solid electrolyte will greatly affect the ionic conductivity of the electrolyte, thereby affecting the battery performance. Summary of the invention

[0005] The object of the present invention is to provide a non-Newtonian fluid quasi-solid electrolyte, a preparation method and an application thereof, so as to solve the problems in the above-mentioned background technology.

[0006] The technical solution adopted by the present invention is: a non-Newtonian fluid quasi-solid electrolyte, wherein the raw materials for preparing the electrolyte include: a basic electrolyte, a shear thickening raw material, a polymerization monomer, a cross-linking agent and a thermal initiator, wherein: the mass ratio of the basic electrolyte to the shear thickening raw material is 20:(1~10).

[0007] Preferably, the basic electrolyte contains a lithium salt, a main solvent and a diluent; the concentration of the lithium salt in the main solvent is 3 to 10 mol / L, and the concentration of the lithium salt in the basic electrolyte is 0.1 to 2.5 mol / L.

[0008] Preferably, the lithium salt includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl imide), lithium hexafluoroarsenate and lithium tetrafluoroborate; the main solvent includes at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether and triethylene glycol dimethyl ether; the diluent includes at least one of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 2,2,2-trifluoroethyl-1,1,2,2-tetrafluoroethyl ether.

[0009] Preferably, the polymerized monomer accounts for 0.5% to 5% of the total mass of the basic electrolyte and the shear thickening raw material, the cross-linking agent accounts for 0.5% to 5% of the total mass of the basic electrolyte and the shear thickening raw material, and the thermal initiator accounts for 0.1% to 0.5% of the total mass of the polymerized monomer and the cross-linking agent.

[0010] Preferably, the polymerizable monomer includes at least one of pentaerythritol tetraacrylate, triethylene glycol dimethacrylate and tetraethylene glycol diacrylate; the crosslinking agent includes at least one of pentaerythritol tetrakis-3-mercaptopropionate, methyl mercaptopropionate, ethyl 3-mercaptopropionate and γ-methacryloxypropyltrimethoxysilane; and the thermal initiator includes at least one of azobisisobutyronitrile, benzoyl peroxide and diphenyloxyethyl percarbonate.

[0011] Preferably, the shear thickening raw material is nano silicon oxide.

[0012] The technical solution of the present invention also includes: a method for preparing the non-Newtonian fluid quasi-solid electrolyte as described above, which comprises the steps of:

[0013] Mix the lithium salt, the main solvent and the diluent according to a certain ratio to obtain a basic electrolyte;

[0014] Mixing the shear thickening raw material and the basic electrolyte according to a certain ratio to obtain a non-Newtonian fluid electrolyte;

[0015] After the polymerization monomer, cross-linking agent and non-Newtonian fluid electrolyte are mixed in a certain proportion, a thermal initiator is added and stirred evenly, and the mixture is allowed to stand for in-situ polymerization to obtain a non-Newtonian fluid quasi-solid electrolyte.

[0016] Preferably, the in-situ polymerization conditions are: temperature 50-85° C., time 8-36 h.

[0017] The technical solution of the present invention also includes: application of the non-Newtonian fluid quasi-solid electrolyte as described above in a metal lithium battery.

[0018] The present invention has the following beneficial effects: the stress caused by the lithium plating / de-lithium of the battery is absorbed by the quasi-solid electrolyte with non-Newtonian fluid characteristics, the volume change of the battery during the charging and discharging process is alleviated, and mechanical hardening occurs rapidly when the battery is subjected to large current pulse charging or sudden external load, so as to inhibit the growth of lithium dendrites and prevent internal short circuits; the polymer network obtained by in-situ polymerization using polymerized monomers, crosslinking agents and thermal initiators can bind the basic electrolyte inside to prevent battery leakage or oxidative decomposition, and can improve the compatibility of the internal interface of the battery, make the interface current uniform, make the deposition and dissolution of metal lithium more uniform, and inhibit the growth of metal lithium dendrites. In addition, since the polymer network obtained by in-situ polymerization has viscoelasticity, the volume change of the battery during the charging and discharging process can be alleviated; the safety performance and cycle performance of the battery can be significantly improved through the synergistic effect of the non-Newtonian fluid and the in-situ polymerized polymer network. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is the electrochemical impedance spectrum measured in Example 1 of the present invention;

[0020] Figure 2 is the electrochemical impedance spectrum measured in Example 2 of the present invention;

[0021] Figure 3 It is the charge and discharge cycle diagram measured by Example 3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0022] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0023] A first aspect of the present invention provides a non-Newtonian fluid quasi-solid electrolyte and a preparation method thereof.

[0024] The raw materials for preparing the non-Newtonian fluid quasi-solid electrolyte in this embodiment include a basic electrolyte, a shear thickening raw material, a polymer monomer, a cross-linking agent and a thermal initiator, wherein: the shear thickening raw material is used to construct the non-Newtonian fluid properties of the electrolyte. Since dendrite growth will accelerate the volume change of the material, the metal lithium will be deposited at the negative electrode during the charging process of the metal lithium battery, which will definitely cause an increase in volume. In the case of uneven current density or uneven lithium nucleation sites on the negative electrode side, the metal lithium will be deposited in a dendritic form. On the one hand, it will cause the surface of the deposited layer to be uneven and not dense, further increasing the volume change. On the other hand, the dendrites may pierce the diaphragm, causing an internal short circuit. The above-mentioned quasi-solid electrolyte with non-Newtonian fluid properties can absorb the stress caused by the lithium plating / de-lithium of the battery, and relieve the battery during the charging and discharging process. The volume change in the battery is rapidly mechanically hardened when the battery is subjected to high-current pulse charging or sudden external load, thereby inhibiting the growth of lithium dendrites and preventing lithium dendrites from penetrating the diaphragm and causing internal short circuits. The polymer network obtained by in-situ polymerization using polymer monomers, cross-linking agents and thermal initiators can bind the basic electrolyte inside to prevent battery leakage or oxidative decomposition, and can improve the compatibility of the internal interface of the battery, make the interface current uniform, make the deposition and dissolution of metal lithium more uniform, and inhibit the growth of metal lithium dendrites. In addition, since the polymer network obtained by in-situ polymerization has viscoelasticity, it can alleviate the volume change of the battery during charging and discharging. Through the synergistic effect of non-Newtonian fluids and in-situ polymerized polymer networks, the safety performance and cycle performance of the battery can be significantly improved.

[0025] The basic electrolyte contains lithium salt, a main solvent and a diluent; the concentration of the lithium salt in the main solvent is preferably 3-10 mol / L, and the concentration in the basic electrolyte is preferably 0.1-2.5 mol / L.

[0026] In this embodiment, the lithium salt can be selected from one or more of lithium perchlorate (LiClO4), lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI), lithium hexafluoroarsenate (LiAsF6), and lithium tetrafluoroborate (LiBF4); the main solvent can be selected from one or more of ethylene glycol dimethyl ether (DME), diethylene glycol dimethyl ether (DEGDME), and triethylene glycol dimethyl ether (G3); the diluent can be selected from one or more of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether (OFE), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), and 2,2,2-trifluoroethyl-1,1,2,2-tetrafluoroethyl ether (HFE).

[0027] The mass ratio of the basic electrolyte to the shear thickening raw material is preferably 20:(1-10), the shear thickening raw material is nano-silicon oxide, and the nano-silicon oxide is preferably silicon oxide particles with a diameter of 1-1000 nm.

[0028] The added amounts of the polymerizable monomer, crosslinking agent and thermal initiator are preferably: the polymerizable monomer accounts for 0.5% to 5% of the total mass of the basic electrolyte and the shear thickening raw material, the crosslinking agent accounts for 0.5% to 5% of the total mass of the basic electrolyte and the shear thickening raw material, and the thermal initiator accounts for 0.1% to 0.5% of the total mass of the polymerizable monomer and the crosslinking agent.

[0029] In this embodiment, the polymerization monomer can be selected from one of pentaerythritol tetraacrylate (PETEA), triethylene glycol dimethacrylate (TEGDMA), and tetraethylene glycol diacrylate (TEGDA); the cross-linking agent can be selected from one of pentaerythritol tetra-3-mercaptopropionate (PETMP), methyl mercaptopropionate, ethyl 3-mercaptopropionate, and γ-methacryloxypropyltrimethoxysilane; the thermal initiator can be selected from one of azobisisobutyronitrile (AIBN), benzoyl peroxide (BPO), and diphenyloxyethyl peroxydicarbonate (BPPD).

[0030] The method for preparing the above-mentioned non-Newtonian fluid quasi-solid electrolyte comprises the following steps:

[0031] (1) mixing the lithium salt, the main solvent and the diluent according to a certain ratio, stirring at room temperature for 8 to 12 hours to obtain a basic electrolyte;

[0032] (2) mixing the shear thickening raw material and the basic electrolyte according to a certain ratio, stirring at room temperature for 8 to 12 hours to obtain a non-Newtonian fluid electrolyte;

[0033] (3) After the polymerization monomer, cross-linking agent and non-Newtonian fluid electrolyte are mixed in proportion, a thermal initiator is added and stirred evenly (10 to 30 minutes), and the mixture is allowed to stand for in-situ polymerization to obtain a non-Newtonian fluid quasi-solid electrolyte.

[0034] In step (3), the conditions for in-situ polymerization are preferably: temperature 50-85° C., time 8-36 h.

[0035] The second aspect of the present invention provides application of the non-Newtonian fluid quasi-solid electrolyte of the first aspect in a metal lithium battery.

[0036] The method for preparing a metal lithium battery using the electrolyte comprises the following steps:

[0037] S1, adding the thermal initiator to the surface of the positive electrode in step (3) and stirring the mixture evenly;

[0038] S2, covering the mixed solution on the positive electrode plate in step S1 with a diaphragm, and coating the surface of the diaphragm with the mixed solution after adding the thermal initiator in step (3) and stirring evenly;

[0039] S3, covering the mixed solution on the diaphragm in step S2 with a metal lithium foil, and using an aluminum-plastic film for overall vacuum packaging;

[0040] S4. The packaged battery is placed at 50-85°C for 12-48 hours for in-situ polymerization to obtain a metal lithium battery.

[0041] The present technical solution is further described below through examples and comparative examples.

[0042] Example 1: Preparation of non-Newtonian fluid quasi-solid electrolyte

[0043] (1) 3.74 g of DME (diluent), 24.07 g of TTE (main solvent), and 5.61 g of LiFSI (lithium salt) were weighed in an argon environment glove box, mixed, and stirred magnetically for 10 h at room temperature to obtain a basic electrolyte;

[0044] (2) adding 3.71 g of nano silicon oxide (shear thickening raw material) to the base electrolyte, and mechanically stirring for 12 h to obtain a non-Newtonian fluid electrolyte; (3) adding 0.1857 g of PETEA (polymer monomer) and 1.39 g of γ-methacryloxypropyltrimethoxysilane (cross-linking agent) to the non-Newtonian fluid electrolyte, and mechanically stirring for 3 h;

[0045] Then, 2.37 mg of AIBN (thermal initiator) was added, and after stirring for 15 min, the mixture was injected into a polytetrafluoroethylene mold with a diameter of 20 mm and allowed to stand at 60 °C for 36 h for in-situ polymerization.

[0046] After cooling to room temperature, the non-Newtonian fluid quasi-solid electrolyte sheet is obtained by demolding.

[0047] The electrochemical impedance spectroscopy of the blocked cell was measured by using sheets of non-Newtonian quasi-solid electrolyte. Figure 1 As shown, the calculated ionic conductivity is 1.97 mS / cm.

[0048] Example 2: Preparation of non-Newtonian fluid quasi-solid electrolyte

[0049] (1) In an argon environment glove box, 7.00 g of G3 (diluent), 20.43 g of OFE (main solvent), and 7.48 g of LiFSI (lithium salt) were weighed, mixed, and magnetically stirred for 12 h at room temperature to obtain a basic electrolyte;

[0050] (2) adding 8.73 g of nano-silicon oxide (shear thickening raw material) to the basic electrolyte and mechanically stirring for 12 h to obtain a non-Newtonian fluid electrolyte;

[0051] (3) Add 1.09 g PEGMEA (polymer monomer) and 1.09 g TEGDMA (cross-linking agent) to the non-Newtonian fluid electrolyte and stir mechanically for 2 h;

[0052] Then, 3.27 mg of AIBN (thermal initiator) was added, and after stirring for 15 min, the mixture was injected into a polytetrafluoroethylene mold with a diameter of 20 mm and allowed to stand at 80 °C for 10 h for in-situ polymerization.

[0053] After cooling to room temperature, the non-Newtonian fluid quasi-solid electrolyte sheet is obtained by demolding.

[0054] The electrochemical impedance spectroscopy of the blocked cell was measured by using sheets of non-Newtonian quasi-solid electrolyte. Figure 2 As shown, the calculated ionic conductivity is 0.85 mS / cm.

[0055] Example 3: Preparation of metal lithium battery

[0056] Preparation of positive electrode sheet: positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O2 ternary material, the positive electrode active material, the conductive agent SuperP and the binder 6wt% polyvinylidene fluoride-hexafluoropropylene are mixed in a mass ratio of 90:5:5, and an appropriate amount of NMP is added for dilution. After stirring evenly, the mixture is evenly coated on a 12μm aluminum foil. After drying, rolling and punching, the positive electrode sheet is obtained.

[0057] Preparation of negative electrode sheet: A lithium foil with a thickness of 60 μm was selected and punched to obtain a negative electrode sheet.

[0058] Diaphragm: Select a double ceramic diaphragm with a thickness of 20μm.

[0059] Metal lithium battery assembly: the mixed solution obtained by adding a thermal initiator and stirring evenly in step (3) of Example 1 is coated on the surface of the positive electrode plate, and a diaphragm is covered on the mixed solution at this time; the mixed solution obtained by adding a thermal initiator and stirring evenly in step (3) of Example 1 is dip-coated on the surface of the diaphragm, and a metal lithium foil is covered on the mixed solution at this time, and an aluminum-plastic film is used for overall vacuum packaging. During the vacuum packaging, the battery is placed in a vacuum oven and evacuated for 3 times, each time maintaining the pressure for 10 minutes (vacuum degree 0.08 MPa) to remove residual air inside the electrode; the packaged battery is allowed to stand at room temperature for 12 hours to achieve further infiltration, and then placed in an oven at 60°C for 36 hours for in-situ polymerization to obtain a metal lithium battery.

[0060] The metal lithium battery was charged and discharged for 70 times, and the charge and discharge curve was measured as shown in the attached figure. Figure 3 As shown, its capacity retention rate is 93.54%.

[0061] Comparative Example 1: Preparation of Metal Lithium Battery

[0062] The only difference compared with Example 3 is that Comparative Example 1 does not use the non-Newtonian fluid quasi-solid electrolyte in Example 3, but uses the basic electrolyte in step (1) of Example 1.

[0063] The metal lithium battery was charged and discharged for 70 times, and the charge and discharge curve was measured as shown in the attached figure. Figure 3 As shown, its capacity retention rate is 85.96%.

[0064] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the claims attached to the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the claims, or the equivalent forms of such scope and boundaries.

Claims

1. A non-Newtonian fluid quasi-solid electrolyte, characterized in that: The raw materials for preparing the electrolyte include: a basic electrolyte, a shear thickening raw material, a polymerizable monomer, a crosslinking agent and a thermal initiator, wherein: the mass ratio of the basic electrolyte to the shear thickening raw material is 20:(1-10).

2. The non-Newtonian fluid quasi-solid electrolyte according to claim 1, characterized in that: The basic electrolyte contains lithium salt, a main solvent and a diluent; the concentration of the lithium salt in the main solvent is 3-10 mol / L, and the concentration of the lithium salt in the basic electrolyte is 0.1-2.5 mol / L.

3. The non-Newtonian fluid quasi-solid electrolyte according to claim 2, characterized in that: The lithium salt includes at least one of lithium perchlorate, lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl imide), lithium hexafluoroarsenate and lithium tetrafluoroborate; the main solvent includes at least one of ethylene glycol dimethyl ether, diethylene glycol dimethyl ether and triethylene glycol dimethyl ether; the diluent includes at least one of 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 2,2,2-trifluoroethyl-1,1,2,2-tetrafluoroethyl ether.

4. The non-Newtonian fluid quasi-solid electrolyte according to any one of claims 1 to 3, characterized in that: The polymerized monomer accounts for 0.5% to 5% of the total mass of the basic electrolyte and the shear thickening raw material, the cross-linking agent accounts for 0.5% to 5% of the total mass of the basic electrolyte and the shear thickening raw material, and the thermal initiator accounts for 0.1% to 0.5% of the total mass of the polymerized monomer and the cross-linking agent.

5. The non-Newtonian fluid quasi-solid electrolyte according to claim 4, characterized in that: The polymerizable monomer includes at least one of pentaerythritol tetraacrylate, triethylene glycol dimethacrylate and tetraethylene glycol diacrylate; the crosslinking agent includes at least one of pentaerythritol tetra-3-mercaptopropionate, methyl mercaptopropionate, ethyl 3-mercaptopropionate and γ-methacryloxypropyltrimethoxysilane; and the thermal initiator includes at least one of azobisisobutyronitrile, benzoyl peroxide and diphenyloxyethyl percarbonate.

6. The non-Newtonian fluid quasi-solid electrolyte according to any one of claims 1-3 and 5, characterized in that: The shear thickening raw material is nano silicon oxide.

7. A method for preparing the non-Newtonian fluid quasi-solid electrolyte according to any one of claims 1 to 6, characterized in that: Includes steps: Mix the lithium salt, the main solvent and the diluent according to a certain ratio to obtain a basic electrolyte; Mixing the shear thickening raw material and the basic electrolyte according to a certain ratio to obtain a non-Newtonian fluid electrolyte; After the polymerization monomer, cross-linking agent and non-Newtonian fluid electrolyte are mixed in a certain proportion, a thermal initiator is added and stirred evenly, and the mixture is allowed to stand for in-situ polymerization to obtain a non-Newtonian fluid quasi-solid electrolyte.

8. The method for preparing a non-Newtonian fluid quasi-solid electrolyte according to claim 7, characterized in that: Conditions for in-situ polymerization: temperature 50-85°C, time 8-36h.

9. Use of the non-Newtonian fluid quasi-solid electrolyte according to any one of claims 1 to 6 in a metal lithium battery.

Citation Information

Patent Citations

  • Solid polymer electrolyte, preparation method thereof and lithium battery

    CN110911739A

  • Ultra-stable interface semi-solid electrolyte battery composite diaphragm and preparation process thereof

    CN112201845A

  • Particle-hybridized polymer solid electrolyte, in-situ polymerization preparation method and application

    CN118040032A

  • Curable electrolyte

    US20080131771A1

Cited By

  • Lithium metal battery low-enthalpy-change high-safety semi-solid electrolyte and preparation method and application thereof

    CN120767402A

  • Battery cell complex, preparation method thereof and all-solid-state battery

    CN121688149A

  • Battery monomer and preparation method thereof, battery device, power utilization device and energy storage device

    CN121938990A